1996
DOI: 10.1097/00000372-199604000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Papulonecrotic Tuberculid in Children

Abstract: Papulonecrotic tuberculid (PNT), a form of cutaneous tuberculosis (TB), is uncommon in children. We identified eight children (six girls and two boys) with PNT. Their ages ranged from 19 to 139 months (median 47.5 months, mean:64.75 months). Skin lesions had been present for 2-24 weeks (median: 4 weeks) before diagnosis. All patients displayed scattered papulo- and/or pustulonecrotic lesions on the limbs, and the ears were involved in six patients. Lesions healed with varioliform scars. Associated pulmonary TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 47 publications
3
42
1
Order By: Relevance
“…It is generally seen in young adults, as in the present study [5,6]. Only one patient had concurrent HIV infection.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…It is generally seen in young adults, as in the present study [5,6]. Only one patient had concurrent HIV infection.…”
Section: Discussionsupporting
confidence: 71%
“…Tuberculids include lichen scrofulosorum (the commonest), erythema induratum of Bazin and papulonecrotic tuberculid. PNT is a rare tuberculidwith very few case series in literature [5,6,7]. Indian data is limited mainly to case reports or to broader studies on cutaneous TB in general [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Jordaan et al reported eight children with papulonecrotic tuberculids (PNT), of which seven had associated pulmonary TB and three had phlyctenular conjunctivitis. [31] It has also been reported in children with active tubercular lymphadenitis and disseminated LV. [32,33] However, PNT has been infrequently reported in Indian children, with only four cases in the series by Vashisht et al [11] Histology shows wedge-shaped necrosis with nonspecific perivascular infiltrates or tubercular granulomas surrounding the necrosis.…”
Section: Tubercular Gummamentioning
confidence: 97%
“…While Vashisht et al and Ramdial and colleagues found vasculitis as a prominent feature in their cases, Jordaan et al did not observe it any of their children with PNT. [11,31,34] Although AFB are not demonstrable in papulonecrotic skin lesions, M. tuberculosis DNA is frequently detected by PCR. [35] Jordaan et al have suggested that in cases where M. tuberculosis DNA can be confirmed by PCR, the term "papulonecrotic tuberculosis" should be preferred over "papulonecrotic tuberculid."…”
Section: Tubercular Gummamentioning
confidence: 99%
See 1 more Smart Citation